The renal cancer risk allele at 14q24.2 activates a novel hypoxia-inducible transcription factor-binding enhancer of DPF3 expression - Protze, Johanna; Naas, Stephanie; Krüger, René; Stöhr, Christine; Kraus, Andre; Grampp, Steffen; Schiffer, Mario; Hartmann, Arndt; Wullich, Bernd; Schödel, Johannes; Wiesener, Michael (Journal of Biological Chemistry, 2022)
Evolution of clear cell renal cell carcinoma is guided by dysregulation of hypoxia-inducible transcription factor (HIF) pathways following loss of the von Hippel-Lindau tumor suppressor protein. Renal cell carcinoma (RCC)-associated polymorphisms influence HIF–DNA interactions at enhancers of important oncogenes thereby modulating the risk of developing renal cancer. A strong signal of genome-wide association with RCC was determined for the single nucleotide polymorphism (SNP) rs4903064, located on chr14q.24.2 within an intron of DPF3, encoding for Double PHD Fingers 3, a member of chromatin remodeling complexes; however, it is unclear how the risk allele operates in renal cells. In this study, we used tissue specimens and primary renal cells from a large cohort of RCC patients to examine the function of this polymorphism. In clear cell renal cell carcinoma tissue, isolated tumor cells as well as in primary renal tubular cells, in which HIF was stabilized, we determined genotype-specific increases of DPF3 mRNA levels and identified that the risk SNP resides in an active enhancer region, creating a novel HIF-binding motif. We then confirmed allele-specific HIF binding to this locus using chromatin immunoprecipitation of HIF subunits. Consequentially, HIF-mediated DPF3 regulation was dependent on the presence of the risk allele. Finally, we show that DPF3 deletion in proximal tubular cells retarded cell growth, indicating potential roles for DPF3 in cell proliferation. Our analyses suggest that the HIF pathway differentially operates on a SNP-induced hypoxia-response element at 14q24.2, thereby affecting DPF3 expression, which increases the risk of developing renal cancer.
CRIS-Team Scopus Importer:2022-03-18